Resolution of peanut allergy: case-control study - Hourihane, Jonathan O’B (BMJ Group, 1998)
Objectives: To determine whether there are any differences between children who remain mildly or moderately allergic to peanut and children with similar histories but a negative reaction on challenge with peanut. Design: Case-controls matched for age and sex. Setting: Children’s day wards in two teaching hospitals. Intervention: Open food challenge with peanut. Subjects: 15 children with resolved peanut allergy (resolvers) and 15 with persistent allergy (persisters). Main outcome measure: Reaction on challenge with peanut, serum total and peanut specific IgE concentrations. Results: The groups had a similar median age at first reaction to peanut (11 months, range 5-38) and similar symptoms. Allergy to other foods was less common in resolvers (2/15) than persisters (9/15) (P=0.02). On skin prick testing with peanut all 13 resolvers tested but only 3/14 persisters had a weal of <6 mm (P<0.0001). Total and peanut specific IgE concentrations did not differ much between the groups. Conclusion: Appropriately trained clinicians must be prepared to challenge preschool children with peanut as some will be tolerant despite a history of reactions to peanut and a positive skin prick test with peanut. Preschool children whose apparent peanut allergy is refuted by food challenge show allergy to other foods less often than those in whom peanut allergy persists. The size of weal on skin prick testing to peanut predicts reactivity but not severity on peanut challenge.